The Role of the Judiciary in Legislating Civil Liability for Damages Caused by Medical Errors - Fayyad, Mahmoud; Mahmoud, Syed (Journal of Legal Sciences, 2022)
This research discussed the role of the UAE high courts in interpreting the legal texts governing the objective civil protection for the injured due to medical errors. It utilized many issued judgments and concluded the importance of these rulings in interpreting the legal texts provided in the relevant legislation. Also, it emphasized the impact of these provisions on the legislative amendments recently made by the UAE legislator, namely the Medical Liability Law No. 4 of 2016 and its Executive Regulation No. 40 of 2019. Although the UAE law does not follow the case law system, this study proved the commitment of the lower courts to the judicial principles issued by these higher courts. The first part highlighted the concept of medical errors in light of the trends of the judiciary. Also, it indicated the scope and nature of the responsibility of healthcare professionals. The part focused on developing the medical liability insurance system in the UAE and interpreting the UAE judiciary for the controls and effects of this insurance. The study concluded the importance of the role of relevant case law in making modern legislative amendments that meet the needs and requirements of health workers in the state.